2018
DOI: 10.1186/s12917-018-1602-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of swab pool size on the detection of influenza A viruses in broiler chickens and its implications for surveillance

Abstract: BackgroundTimely diagnosis of influenza A virus infections is critical for outbreak control. Due to their rapidity and other logistical advantages, lateral flow immunoassays can support influenza A virus surveillance programs and here, their field performance was proactively assessed.The performance of real-time polymerase chain reaction and two lateral flow immunoassay kits (FluDETECT and VetScan) in detecting low pathogenicity influenza A virus in oropharyngeal swab samples from experimentally inoculated bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Within-flock models of HPAI spread have been used to inform several risk management decisions such as the choice of active surveillance protocol options for early detection (see, e.g. [4]). The implications of improved estimation of parameters for such within-flock models are beneficial to the improved prevention of between-flock transmission [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Within-flock models of HPAI spread have been used to inform several risk management decisions such as the choice of active surveillance protocol options for early detection (see, e.g. [4]). The implications of improved estimation of parameters for such within-flock models are beneficial to the improved prevention of between-flock transmission [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…(i) Sample pooling for rRT-PCR. Sample pooling was first suggested by Robert Dorfman in 1943 as a way of optimizing syphilis testing, and since then, it has been applied in surveillance and screening for infections such as human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), malaria, and influenza virus (19)(20)(21)(22)(23)(24)(25). Sample pooling has popularly been employed in serological work but also in molecular diagnostics and research.…”
mentioning
confidence: 99%
“…To maintain the country’s international status as the largest export producer of ostrich products, South African farmers must adhere to strict bio-security requirements and undertake rigorous and costly testing to prove freedom of IAV infection. Pooling 5 ostrich tracheal swabs is the current standard practice as pooling increases not only testing throughput, but it also reduces the number of tests needed to meet sample size requirements and consequently the test costs [ 9 , 13 ]. Pools of up to 11 swabs for chicken or turkey swabs are validated and used internationally [ 7 , 9 , 11 , 13 , 14 ], therefore in the current study we investigated the effects of also increasing ostrich tracheal swab pools to 10.…”
Section: Discussionmentioning
confidence: 99%
“…Pooling 5 ostrich tracheal swabs is the current standard practice as pooling increases not only testing throughput, but it also reduces the number of tests needed to meet sample size requirements and consequently the test costs [ 9 , 13 ]. Pools of up to 11 swabs for chicken or turkey swabs are validated and used internationally [ 7 , 9 , 11 , 13 , 14 ], therefore in the current study we investigated the effects of also increasing ostrich tracheal swab pools to 10. Our results showed that increasing the ostrich swabs to 10 per pool had no detrimental effect on the sensitivity of the RT-rtPCR assay in detecting H5N8 HPAIV or H7N1 LPAIV; and doubling the swab pool size even seemed to improve the sensitivity of IAV detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation